David Bohm’s theory of hidden variables - Pabjan, Tadeusz (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2009)
One of the most important interpretative problems of quantum mechanics concerns the so called hidden variables. Sometimes it is said that the Bell’s theorem falsifies theories of such variables, but in fact, it falsifies only local ones. This paper deals with David Bohm’s interpretation of quantum mechanics, which is a kind of nonlocal hidden variable theory. This theory delivers a full deterministic and realistic description of quantum phenomena and predicts the same results as standard quantum mechanics. It is argued that this interpretation is still worth being investigated, because it remains in the full agreement with the mathematical formalism of this theory and it surpasses the standard interpretation as far as simplicity and lack of arbitrary assumptions are concerned.